Nutritious Sweetpotato for Niassa and Inhambane, Mozambique - International Potato Center (2017)
Nutritious Sweetpotato for Niassa expands into the Province of Inhambane in Mozambique. The project started a new one-year interim phase in January 2017 after successfully completing Phase 1. In Niassa province, we continued to work in the same eight intervention districts and extended to three districts of Inhambane province to develop a second four-year phase that will commence in 2018. A participatory training was planned in collaboration with Provincial Director of Agriculture and Food Security (DPASA) and implemented by District Economic Activity (SDAE) extension personnel in 110 villages in the two provinces.